The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1046/j.1432-1327.1998.2540626.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an α‐2,6‐sialylated lipooligosaccharide from Neisseria meningitidis immunotype L1

Abstract: The recent cloning of the lipooligosaccharide (LOS) A-2,3-sialyltransferase from Neisseria meningitidis immunotype L3 permitted us to examine other immunotypes for this structural gene. We identified the gene and measured the enzyme activity in the L1 immunotype strain which had previously been reported to lack sialic acid in its LOS because it contains a terminal A-linked galactose which was thought not to be an acceptor for the sialyltransferase. This finding prompted us to re-examine the structure of the LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 6 publications
2
47
1
Order By: Relevance
“…In contrast, the three proton resonances assigned to H-5, H-6a, and H-6b showed downfield chemical shift values, indicating acetylation at O-6. These results are in agreement with previous reports of 1 H NMR assignment studies that showed meningococcal LOS to be acetylated at O-6 of GlcNAc (41,42).…”
Section: Analysis Of Petn Substitution By Maldi-tof Mass Spectrometrysupporting
confidence: 94%
“…In contrast, the three proton resonances assigned to H-5, H-6a, and H-6b showed downfield chemical shift values, indicating acetylation at O-6. These results are in agreement with previous reports of 1 H NMR assignment studies that showed meningococcal LOS to be acetylated at O-6 of GlcNAc (41,42).…”
Section: Analysis Of Petn Substitution By Maldi-tof Mass Spectrometrysupporting
confidence: 94%
“…Genomic and Allelic Differences in LOS Biosynthetic GenesTo lend support for our conclusions of correlations between LOS structure and disease outcome, we analyzed the sequence diversity of LOS biosynthetic genes in a very large database of meningococcal genomes (32,202 genomes) found at the Pub-MLST website. The average number of unique alleles for the seven genes used for multilocus sequence typing was 529 alleles/gene (data not shown).…”
Section: Differences In Os Structures Of Los Between Invasive Andmentioning
confidence: 94%
“…OS Compositions-A number of groups, including our own, have studied the structure of the OS from N. meningitidis (1, 23, 24,26,32,33). Compositions for the OS were assigned based on peaks we detected, the previously reported structures, and using the following potential components: 2 Kdo, 2 Hep, 1 or more Hex, and 1 or more HexNAc, 0 -1 Neu5Ac, 0 -1 O-Ac, 0 -1 O-Gly, and 0 -2 PEA.…”
Section: Relative Abundance Of Lipid a Phosphoforms Correlates With Tmentioning
confidence: 99%
“…4). PCR amplification was performed to determine if the genes lpt6 and lpt3 were present in the N. meningitidis LPS immunotyping reference L1 to L10 strains, for each of which the LPS structure has been characterized (11,13,22,29,35,36,49). The lpt6 gene was found in the L2, L4, L6, and L10 strains, and lpt3 was present in the L1, L3, L7, L8, and L9 strains.…”
Section: Vol 186 2004 the Lpt6 Gene In N Meningitidis And H Influmentioning
confidence: 99%